The Role of Ethnomathematics in Enhancing Contextual Mathematics Understanding Among Students - Yanti, Sepni (PT Maju Malaqbi Makkarana, 2025)
Ethnomathematics integrates cultural practices with mathematical concepts, offering a contextualized approach to mathematics education. This literature review explores the role of ethnomathematics in improving students’ understanding of contextual mathematics by analyzing previous research on incorporating cultural elements into learning processes. The findings suggest that ethnomathematics enhances student engagement by connecting mathematics to real-life cultural practices, fostering critical thinking, and improving problem-solving skills. This approach helps make abstract mathematical concepts more accessible and meaningful, particularly for students from diverse cultural backgrounds. Moreover, it supports the preservation of cultural heritage while addressing the challenges posed by standardized and globalized education systems.Despite its benefits, implementing ethnomathematics faces challenges, including limited culturally tailored resources, insufficient teacher training, and difficulties in aligning with standardized curricula. Addressing these obstacles requires developing culturally responsive teaching materials and enhancing educators' familiarity with diverse cultural contexts. This review emphasizes the importance of ethnomathematics as an innovative approach to creating inclusive and equitable mathematics education. It also highlights the need for further research and practical applications to maximize its potential in preserving cultural identity and enriching mathematics learning experiences.